2019
DOI: 10.1111/apa.14836
|View full text |Cite
|
Sign up to set email alerts
|

Worse global intellectual and worse neuropsychological functioning in preterm‐born children at preschool age: a meta‐analysis

Abstract: Aim Preterm births (<32 weeks of gestational age) are associated with cognitive problems that are difficult to diagnose in infancy but potentially detectable at preschool age. This review aimed to evaluate the extent to which total intelligence quotient (IQ) and neuropsychological functions at ages three to five years differ between children born at <32 weeks gestational age or < 1500 g birth weight and children born at term. The secondary aim was to determine whether cognitive performance differs between extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 49 publications
4
52
0
Order By: Relevance
“…Authors searched Medline, [1][2][3][4][5] Embase, 1,2 PsychInfo 1,3-5 and WoS, 3,4 using different search terms.…”
Section: Resultsmentioning
confidence: 99%
“…Authors searched Medline, [1][2][3][4][5] Embase, 1,2 PsychInfo 1,3-5 and WoS, 3,4 using different search terms.…”
Section: Resultsmentioning
confidence: 99%
“…The research focus has been on factors affecting neurodevelopment in the most immature infants 5 and less is known about long‐term outcomes for more mature very preterm infants, with a GA of 28‐31 weeks, who were born in the 2000s 6‐8 . Although these children are expected to have better outcomes than the extremely preterm children, they still have higher risks of neurodevelopmental difficulties than term‐born children 2,6 …”
Section: Introductionmentioning
confidence: 99%
“…Still, the risks of neonatal complications continue to be relatively high, especially in extremely preterm infants with gestational ages (GA) below 28 weeks, and there are no indications of improvements in neurodevelopmental outcomes 3,4 . The research focus has been on factors affecting neurodevelopment in the most immature infants 5 and less is known about long‐term outcomes for more mature very preterm infants, with a GA of 28‐31 weeks, who were born in the 2000s 6‐8 . Although these children are expected to have better outcomes than the extremely preterm children, they still have higher risks of neurodevelopmental difficulties than term‐born children 2,6 …”
Section: Introductionmentioning
confidence: 99%
“…These correlations confirm the evidence from studies on both transparent [ 13 , 16 ] and opaque [ 1 , 2 , 18 , 22 ] languages. They also confirm the usefulness of exploring the neurocognitive domains, and in particular, those that are inherent to the executive functions, to identify therapeutic and preventive interventions from preschool age [ 11 , 57 , 58 ]. For EP children relative to term-born controls from school entry through adolescence, Johnson et al [ 2 ] reported significant deficits in a range of basic cognitive processes, which included short-term memory, processing speed, visual-perceptual skills, sensorimotor integration and attention [ 2 ].…”
Section: Discussionmentioning
confidence: 61%
“…It is worth noting that among the neurocognitive domains, only visual-motor skills were correlated to IQ. This suggests the importance of long-term neurocognitive follow-up even if the children have an IQ within the normal range [ 1 , 11 , 13 , 58 , 59 , 60 , 61 ]. Nevertheless, in agreement with the literature, the IQs were correlated with text comprehension [ 12 , 13 , 27 , 32 , 48 , 62 ].…”
Section: Discussionmentioning
confidence: 99%